Predictors of Tooth Brushing Behavior in Iranian Adolescents: an Application of the Planned Behavior Theory - Amir Pakpour Hajiagha; Mohsen Saffari (Islamic Dental Association of Iran, 2012)
Background and Aim: Contrary to thetheory of planned behavior (TPB), intention alone is not sufficient to predict behavior. The aim of the study was application of anextended model of planned behavior in predicting dental brushing behavior among a sample of adolescents in Qazvin .   Materials and Methods: A number of 383 adolescents participated in thiscross-sectional study. Attitude, subjective norm, perceived behavior control, action and coping scales and a self report questionnaire regarding dental brushing behavior was completed by the adolescents. Data were analyzed by a confirmatory factor analysis (CFA) on an original six-factor structure (attitude, subjective norms, perceived behavior control, intention, action plan and coping plan) and also a hierarchical linear regression analysis .   Results: The mean age of the adolescents was 15.41 years. The most of the student were male (50.2). The CFA for the original six-factor structure showed a good fit index (λ2 = 645.25, degrees of freedom df=309, goodness-of-fit index (GFI) =90, root mean squared error of approximation (RMSEA) =0.054). Action- and coping planning aggregately accounted for 11.1% of the variance associated with dental brushing behavior .   Conclusion: Results obtainedform CFA analysis approved the six-factor structure including intention, action plan and coping plan . Action plan and coping plan can reduce intention-behavior gap .